Organ‐based clues for diagnosis of inborn errors of immunity: A practical guide for clinicians - Fatemeh Mohammadi; Amirhossein Yadegar; Mahta Mardani; Aryan Ayati; Hassan Abolhassani; Nima Rezaei (Immunity, Inflammation and Disease)
Abstract Inborn errors of immunity (IEI) comprise a group of about 490 genetic disorders that lead to aberrant functioning or the development of distinct immune system components. So far, a broad spectrum of IEI‐related manifestations has been noted in the literature. Due to overlapping signs and symptoms of IEI, physicians face challenges in appropriately diagnosing and managing affected individuals. The last decade has witnesses improving in the molecular diagnosis of IEI patients. As a result, it can be the mainstay of diagnostic algorithms, prognosis, and possibly therapeutic interventions in patients with IEI. Furthermore, reviewing IEI clinical complications demonstrates that the manifestations and severity of the symptoms depend on the involved gene that causes the disease and its penetrance. Although several diagnostic criteria have been used for IEI, not every patient can be explored in the same way. As a result of the failure to consider IEI diagnosis and the variety of diagnostic capabilities and laboratory facilities in different regions, undiagnosed patients are increasing. On the other hand, early diagnosis is an almost essential element in improving the quality of life in IEI patients. Since there is no appropriate guideline for IEI diagnosis in different organs, focusing on the clues in the patient's chief complaint and physical exams can help physicians narrow their differential diagnosis. This article aims to provide a practical guide for IEI diagnosis based on the involved organ. We hope to assist clinicians in keeping IEI diagnosis in mind and minimizing possible related complications due to delayed diagnosis.